Examination of the Addictive and Behavioral Properties of Fatty Acid-Binding Protein Inhibitor SBFI26 - Thanos, Panayotis K.; Clavin, Brendan H.; Hamilton, John; O’Rourke, Joseph R.; Maher, Thomas; Koumas, Christopher; Miao, Erick; Lankop, Jessenia; Elhage, Aya; Haj-Dahmane, Samir; Deutsch, Dale; Kaczocha, Martin (Frontiers in Psychiatry, 2016)
Abstract: The therapeutic properties of cannabinoids have been well demonstrated but are overshadowed by such adverse effects as cognitive and motor dysfunction, as well as their potential for addiction. Recent research on the natural lipid ligands of cannabinoid receptors, also known as endocannabinoids, have shed light on the mechanisms of intracellular transport of the endocannabinoid anandamide by fatty acid binding proteins (FABPs) and subsequent catabolism by fatty acid amide hydrolase (FAAH). These findings facilitated the recent development of SBFI26, a pharmacological inhibitor of epidermal- and brain-specific FABP5 and FABP7, which effectively increases anandamide signaling. The goal of this study was to examine this compound for any possible rewarding and addictive properties as well as effects on locomotor activity, working / recognition memory, and propensity for sociability and preference for social novelty given its recently reported anti-inflammatory and analgesic properties. Male C57BL mice were split into four treatment groups and conditioned with 5.0 mg/kg, 20.0 mg/kg, 40.0 mg/kg SBFI26 or vehicle during a conditioned placed preference (CPP) paradigm. Following CPP, mice underwent a battery of behavioral tests (open field, novel object recognition (NOR), and social interaction (SI) and novelty (SN)) paired with acute SBFI26 administration. Results showed that SBFI26 did not produce conditioned placed preference or conditioned place aversion regardless of dose, and did not induce any differences in locomotor and exploratory activity during CPP or SBFI26-paired open field activity. We also observed no differences between treatment groups in NOR, SI, and SN. In conclusion, as SBFI26 was shown previously by our group to have significant analgesic and anti-inflammatory properties, here we show that it does not pose a risk of dependence or motor and cognitive impairment under the conditions tested.